$\displaystyle -\frac{\pi}{4}=arctan(\frac{\frac{-2L}{3}}{R})\\$ why it equals $\displaystyle \frac{\frac{-2L}{3}}{R}=-1$ ?
Follow Math Help Forum on Facebook and Google+
Originally Posted by transgalactic $\displaystyle -\frac{\pi}{4}=arctan(\frac{\frac{-2L}{3}}{R})\\$ why it equals $\displaystyle \frac{\frac{-2L}{3}}{R}=-1$ ? By taking "tan" for the both sides of the first equation.
I'm not sure what you are asking. $\displaystyle \arctan(x)=-\pi/4$ has just one solution, which is $\displaystyle x=-1$.
View Tag Cloud